Offer Elaboration: New Confidence Indexes to take into account Uncertainty. Issue 1 (July 2017) - Sylla, A.; Vareilles, E.; Coudert, T.; Aldanondo, M.; Geneste, L.
Abstract: In order to respond to a call for tenders, bidders must define and evaluate potential solutions, based upon the specifications of customer's requirements and their capabilities (skills, existing solutions, resources … etc.). The definition and the evaluation of potential solutions are not trivial activities. The lack of relevant information makes the evaluation imprecise and uncertain. Therefore bidders choose the most suitable solution based upon the standard indicators (cost, performance and lead time) and their subjective feeling. Unfortunately, this may leads to the choice of unfeasible solution regarding customer's expectations (cost, performance and delivery time). Therefore, the aim of this paper is twofold: (i) first, to clarify the notion of imprecision and uncertainty in the evaluation of potential solutions; and (ii) second, to propose two Confidence Indexes (CI) in order to take into account uncertainty in offer elaboration. The first one (CIS ) characterizes the confidence in the technical system solution and the second one (CIP ) the confidence in the implementation process of the technical system. The proposed CIS and CIP will enable bidders to choose the most relevant solution not only based upon the standard indicators but also considering the confidence in the potential solutions.